Examining the Effects of Forest Fires: A Framework for Integrating System Dynamics and Remote Sensing Approaches - Eriş, Müjgan Bilge; DEMİREL, DUYGUN FATİH; Sezer, Eylül Damla Gönül (IGI Global, 2024)
Forest fires have been a major concern for many countries over an extended period of time due to natural and human induced factors. In recent years, detection of forest fires has progressively shifted toward advanced technologies where the remote sensing approaches are fully operational. To enhance fire management strategies, it is crucial to gain a comprehensive understanding of the fire dynamics and its consequences on the environment, operational sources, and economic sectors. Therefore, this chapter develops an integrated framework to predict and analyze the effects of forest fires by using system dynamics approach and remote sensing technology, ultimately leading to the establishment of a conceptual model and conclusive insights. © 2024, IGI Global. All rights reserved.
Sensors for Environmental Monitoring, Identification, and Assessment